R. C. Geary, M. D. MacCarthy, A. G. Kendall "Elements of Linear Programing with Economics Applications Being number fifteen of Griffin’s Statistical, Monographs and Courses" - Uribe Villegas, Óscar (Revista Mexicana de Sociología, 1968)
reseña